(untitled) (African Journal of Biomedical Research, 2021)
Cassava seed oil obtained from Manihot esculenta Crantz possesses antimicrobial and anti-oxidant properties and can be incorporated in topical pharmaceutical formulations for treatment of wounds, skin infections and irritations. This work determined the effects of formulation variables on the properties of cassava seed oil microcapsules and the antimicrobial properties of its cream formulations. Cassava seed oil was formulated into alginate microcapsules using calcium chloride and aluminum sulphate as cross-linkers at varying oil:alginate ratios, cross-linker concentrations, and curing times. The surface morphologies, particle sizes, encapsulation efficiencies (EE) and FT-IR spectra of the microcapsules were determined. Selected microcapsules were formulated into creams and the antimicrobial activities of the cream formulations were determined against Acinetobacter baumannii NCTC 7363, Serratia marcescens ATCC 8155, Staphylococcus aureus ATCC 29213, Citrobacter freundii ATCC 8090, Escherichia coli ATCC 25925, Salmonella typhimurium 14028, Pseudomonas aeruginosa 27853 and Staphylococcus aureus ATCC 6571 by agar diffusion. Microcapsules crosslinked with calcium chloride were smaller with smoother surfaces, while those with aluminum sulphate were large, irregularly shaped with rough surfaces. The EE of microcapsules crosslinked with aluminum sulphate were higher than those with calcium chloride. The EE (23.6 – 66.7%) increased with increase in alginate:oil ratio, concentration of cross-linkers and curing times. The oily cream retained its antimicrobial property against many of the microorganisms, showing highest inhibitory activities against Pseudomonas aeruginosa 27853 and Acinetobacter baumannii NCTC 7363. Creams incorporating Cassava seed oil microcapsules with antimicrobial and antioxidant properties were produced using a simple microencapsulation process with biodegradable and renewable materials.